Youth Perspective of Middle Students on Disaster Management Using the Simulation Method in Increasing Resiliency - Sri Sumartini; Sehabudin Salasa; Linda Amalia (NurseLine Journal, 2023)
Indonesia is a country that is located between two continents and two oceans, where the volcanic mountain paths meet, namely the Pacific Circum and the Mediterranean Circum, is one of the countries that has a large enough disaster potential. But on the other hand, this condition has a logical consequence that Indonesia is a country that has a high level of vulnerability to natural disasters. West Java itself is one of the areas prone to natural disasters. The National Disaster Management Agency (BNPB) stated that there were 8 provinces that were most frequently hit by disasters during the 2016 period, West Java ranked third after Central Java and East Java.Analyze the level of resilience of disaster management before and after being given the Simulation method and knowing the role of high school students in disaster management using the simulation method. The research method used a quantitative analysis design, with a Quasi Experimental research design with Pre and Post-Experimental measuring the resilience of students who received simulation exercises without a control group. Sampling used the Simple Random Sampling technique with the criteria of Grade 10 and Grade 11 students as many as 30 students at SMA Negeri I Parongpong, Lembang, West Badung Regency. The instrument used in the study used the Connor-Davidson Resilience Scale (CD-RISC) questionnaire. The results of the study showed that there were differences in the perceptions of youth in disaster management and the role of senior high school students in resilience before and after the stimulation method was used. The simulation method is more effective in increasing resilience to disaster management.